GAMBARAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SEKOLAH MENENGAH ATAS NEGERI 11 AMBON TAHUN 2023 - Muliati Muliati (PAMERI, 2023)
Breast cancer is a disease characterized by the presence of abnormal cells that can grow uncontrollably and havethe ability to attack and move between cells and tissues of the body. Breast cancer is one of the non-communicable diseases that most often causes death in women. Women who are late aware of the changes that occur in the breast make the prognosis even worse. The importance of breast cancer screening can be started from oneself because 85% of all breast changes can be well recognized by sufferers through breast self-examination (BSE). BSE is effective if it is done when you are at your childbearing age, namely at the age of 15-49 years which can be done on the 7th-10th day which is counted from the 1st day of menstruation. The low awareness of women is due to a lack of knowledge about BSE as a result of a lack of information, education and motivation. The purpose of this study was to see an overview of the level of knowledge, attitudes and behavior of young women regarding breast self-examination (BSE) at State High School 11 Ambon. There were 141 grade 12 students who were respondents in this study. This research is a quantitative descriptive study with a cross sectional approach. Sampling using total sampling method. The results showed that most of the respondents had sufficient knowledge (53.2%), negative attitudes (65.2%) and rare BSE behavior (89.4%). Based on the research results, it is suggested that further researchers can analyze the relationship between knowledge and attitudes towards BSE behavior.